Papuan Pictures - Dauncey, H. M., 1863-1932 (Salt Lake City, UT : Project Gutenberg, 2018)
"Papuan Pictures" by H. M. Dauncey is a collection of observational writings and reflections on life in Papua, created during the early 20th century. The work vividly describes various aspects of the everyday lives of the Papuan people, including their customs, games, education, and societal structures, through the eyes of the author who spent many years living in the village of Delena. The opening of the text introduces readers to the village of Delena and specifically emphasizes the playful and carefree nature of its children. Dauncey met with young Papuans as they joyfully greeted newcomers and engaged in their unique forms of play, which include games reminiscent of those played in western countries as well as traditional activities. He also highlights cultural practices such as hair cutting traditions associated with childhood, the affectionate demeanor of parents, and the lively celebrations that occur when a child is born, all intricately woven into a rich tapestry that illustrates life in this remote community. The opening serves as an affectionate introduction to Dauncey$1 (Bs observations on the interplay between tradition and the influences of missionary education amongst the children of Delena. (This is an automatically generated summary.)s
Games and school -- The conceited youth -- Keeping house -- Grandfather and grandmother -- The sorcerer -- A sandalwood church, and an incident -- A chapter of accidents -- A feast and a dance -- How we go -- Korona, a hillside village -- Kabadi -- A Christmas gathering -- Doctoring -- Peace-making -- Some pictures of life -- The aim.
Release date is 2018-08-21
E-text prepared by Bryan Ness and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Papuans; Missions -- Papua New Guinea